Kajian Mutu Ikan Layang (Decapterus russelli) Segar di Pasar Tuminting Kota Manado - Umpain, Johannis; Wonggo, Djuhria; Sanger, Grace (Media Teknologi Hasil Perikanan, 2014)
The aim of the research was to observe the freshness of flying fish (Decapterus russelli) in Pasar Tuminting, Manado, North Sulawesi. The highest pH degree of D. ruselli was 5.6 and the lowest was 5.4. The range of TVB value was 28.01–14 mg N/100 g of flesh. The organoleptic test on eyes, mucus, gill, texture and odour approximately was 6. The conclusion of the research was flying fish in Pasar Tuminting was still fresh. Keywords: Flying fish, Decapterus russelli, pH, TVB, organoleptic.